On oscillation of nonlinear second-order differential equations with damping term - Mustafa, OG; Rogovchenko, SP; Rogovchenko, YV (Academic Press Inc Elsevier Science, 2004)
The paper is concerned with oscillation of a novel class of nonlinear differential equations with a damping term. First it is demonstrated how known oscillation results for another intensively studied class of equations can be translated to the one in question, and vice versa. Advantages and drawbacks of such translation are carefully examined. Then an oscillation criterion for the new class of equations is established. The principal result of the paper is compared to those reported in the literature, and an illustrative example to which known oscillation criteria fail to apply is provided. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: nonlinear differential equations; second order; nonlinear damping term; oscillatory solutions; integral transformation